Measurement studies in sports science research - Pyne, D. B. (International Journal of Sports Physiology and Performance, 2008)
Each year, the International Journal of Sports Physiology and Performance (IJSPP) receives several reliability or validity manuscripts for publication. This type of manuscript appears widely in the sports science literature. Most graduate students encounter the issue of reliability and validity at some point in their research studies, often culminating in preparation and submission of a manuscript to a peer-reviewed journal. We offer some guidance for authors and readers of measurement studies based on our editorial experience at IJSPP.